Bureaucrats and Bourgeois Society - Kingston, R. author. aut Link
X, 237 p.
Keywords: Between 1789 and 1848, clerks modified their occupational practices, responding to political scrutiny and state-administration reforms. Ralph Kingston examines the lives and influence of bureaucrats inside and outside the office as they helped define nineteenth-century bourgeois social capital, ideals of emulation, honour, and masculinity.